Dinâmica hidroclimática e tipos de clima da serra de Baturité (CE) - Silva Neto, José Augusto da (2020)
The humid mountains ranges of Northeast Brazil are topographically elevated surfaces dispersed in the semiarid climate domain and which are subjected to altitude mesoclimates. The Baturité’s mountain is one of the most expressive compartments of the Ceará relief and is endowed with environmental aspects that are very characteristic and that are processed according to the hydroclimatic differentiations provided by the mountain environment. Given this scenario, the present research has as main objective to carry out an analysis on the hydroclimatic dynamics of the Serra de Baturité and on the typologies of climate that originate from this dynamics. For this, approaches and methods of analysis from Geographical Climatology were adopted throughout the historical series from 1989 to 2018, in which the rhythm and genesis of thermopluviometric characteristics were prioritized over the use of their average values. In this sense, the concept of types of annual climates (TAC) was applied based on the climatic classification indexes of Thornthwaite and Mather (1955) which are based on the values of the climatological water balance. Based on this, a proposal was made for classification and mapping by means of the climatic types that occurred more frequently. In the main results obtained, it was observed that the locations located in the highest compartments presented milder temperatures and potential evapotranspiration rates, in addition to higher, less irregular rainfall and with longer rainy periods than those located in the surrounding mountains. The analysis and mapping of the most frequent TACs demonstrated that: the Semiarid (D1d) occurred more frequently in the semiarid piemont (leeward); the Semiarid (D2d2) occurred more frequently in the sub-humid piemont (windward); the Subhumid dry (C1a2) was the most recurrent climate in the southern and central portion of the plateau, as well as in the areas with more modest levels of the wet dissected side; the Sub-humid humid climate (C2p2) was the most frequent in the highest northern portion of the wet dissected slope; the Humid climate (B1p) occurred more frequently in the northern portion of the plateau; and the Perhumid climate (Ar2) in the upper areas of the northern portion of the plateau.